Perceived Stress, Stressors, and Coping Mechanisms among Doctor of Pharmacy Students - Jennifer W. Beall; Renee M. DeHart; Robert M. Riggs; John Hensley (MDPI AG, 2015)
The primary purpose of this study was to examine perceived stress in doctor of pharmacy students during their first, second, and third years of their program in a fully implemented new curriculum. The secondary objectives were to determine if there is a relationship between perceived stress and certain demographic variables, to compare student pharmacist perceived stress to the perceived stress in the general population, and to examine student reported stressors during pharmacy school and coping strategies employed for those stressors. A previously validated survey (Perceived Stress Scale-10) was given to first, second, and third year student pharmacists. Females exhibited higher mean stress scores than males. The under 22 years and over 32 years age categories exhibited higher mean stress scores than the 22 to 26 year old student population. There was no significant difference in perceived stress scores between classes of the program. Only a portion of the variation in stress scores was predicted by gender, age, marital status, race, and year in curriculum. Stress scores among these student pharmacists are higher overall than those in previously published probability samples in the general population. Class assignments and completing electronic portfolios were the top stressors reported. Spending time with family and friends was the most frequent coping mechanism reported. Programming related to stress reduction (particularly among female and nontraditional age students) appears warranted.